(untitled) (REMUNOM, 2025)
Hepatic cirrhosis is a chronic, progressive, and irreversible disease characterized by the replacement of normal liver tissue with fibrous tissue, resulting in loss of liver function. Its main causes include excessive alcohol consumption, viral hepatitis types B and C, and non-alcoholic steatohepatitis (NASH). Among the most frequent complications is malnutrition, manifested by sarcopenia and loss of body fat, resulting from hepatic dysfunction, metabolic alterations, and malabsorption of nutrients. Nutritional support is essential in clinical management, as it improves liver function, reduces hospitalization time, and contributes to the prevention of hepatic encephalopathy. The diet should be hypercaloric, rich in vitamins and minerals, with adequate protein intake and sodium restriction, aiming to control ascites and maintain metabolic balance. In this context, the pharmacist plays a fundamental role in guiding the rational use of medications and the interaction between pharmacological therapy and diet, promoting comprehensive patient care. This work, based on a literature review conducted in the Google Scholar and SciELO databases between 2007 and